Caracterización morfoestructural y faneroptico del bovino criollo en la provincia de Manabí - Díaz Ruiz, René Javier (2013)
The work was carried out in the province of Manabí in 22 cantons, the objective of this study was to evaluate the variable zoometric and faneropticas of Creole in the province of Manabí, Ecuador, cattle in a sample of 167 Creole UBAS and 167 UBAS of other races with a mixture of (Browm swiss, jersey and brahman), measured 16 variable zoometric and nine characters faneropticoseach of the animals in the study, their body measurements or variable zoometric quantitative nature, through the measuring tape and cane zoometric in both races took them as it is; Width of the head (ACF); Length of the head (LCF); Length of face (LR); Length of the skull (LC); Height at the Withers (ACR); Bicostal diameter (DB); Distance between meeting (DE); Diameter (DD) sternal back; Perimeter of the chest (PT); Perimeter of the Shank (PC); Occipital length - Ischial (LOI); Show of hands at the entrance of the rump (AEG); Rear width of the Croup (AG); Length of the rump (LG); Width weight (Kg) and inter - iliac (AII). The results obtained from the 16 biometric measurements provided important data to differentiate from other animals, to group them into specific sets and, fundamentally, to deduce the proportions that in turn indicate functional skills. The significant difference (P < 0.05) from measurements of animals for study, regarding other authors, is given by the fact, that (local) Creole animals of small size, were used in this investigation with a deficient diet and a null sanitary management of them, as well as the European races this last having no favorable response, the qualitative variables show results that determine a predominance of short hair (100%) in both races and a tendency to color Colorado whole in the Criollo (20.36%) and white at the European race (51,49%); the population under study showed a straight profile in Creole and European breeds of (94.61 and 41.92% respectively), presence of hump in the European race (11.98%) with high percentage of horizontal criollo cattle ears of (89,82%) and at the European race of drooping ears (88.02%).